2021
DOI: 10.1177/2158244021990656
|View full text |Cite
|
Sign up to set email alerts
|

Phishing for Long Tails: Examining Organizational Repeat Clickers and Protective Stewards

Abstract: Organizational cybersecurity efforts depend largely on the employees who reside within organizational walls. These individuals are central to the effectiveness of organizational actions to protect sensitive assets, and research has shown that they can be detrimental (e.g., sabotage and computer abuse) as well as beneficial (e.g., protective motivated behaviors) to their organizations. One major context where employees affect their organizations is phishing via email systems, which is a common attack vector use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 38 publications
0
10
1
Order By: Relevance
“…No significant interactions (in click-rates or report-rates) between the email template types and job role were observed. Overall, the click-rates were relatively low compared to previously observed campaigns (Canham et al, 2021). This might have been the result of a self-selected sample of participants with knowledge of their contest participation.…”
Section: Resultscontrasting
confidence: 68%
See 2 more Smart Citations
“…No significant interactions (in click-rates or report-rates) between the email template types and job role were observed. Overall, the click-rates were relatively low compared to previously observed campaigns (Canham et al, 2021). This might have been the result of a self-selected sample of participants with knowledge of their contest participation.…”
Section: Resultscontrasting
confidence: 68%
“…Complementing the research on human-detection capabilities, recent efforts have drawn attention to all potential employee behavioral responses to email phishing attacks (Canham et al, 2021). By analyzing the responses of more than 6,000 employees at a large U.S. university over the course of 20 phishing training campaigns and 19 months, this effort demonstrated that a small subset of users (6% of the total population of users) were responsible for repeated phishing training failures (i.e., "Repeat Clickers") and a larger subset (33%) of users ("Protective Stewards") were responsible for reporting these emails to the Information Security Office.…”
Section: Background On Phishingmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2021, Canham et al 30 investigated phishing related behaviors at a southeastern university in the United States. The focus for this study was on determining employee cluster types for responses to phishing attacks based on positive and negative actions.…”
Section: Phishing Related Behaviorsmentioning
confidence: 99%
“…Canham et al noted that security training is "as expected" not perfect as even in the Beacon and Spectator clusters, around 3-4% of the employees fell victim. 30…”
Section: Phishing Related Behaviorsmentioning
confidence: 99%